HUBUNGAN TEKANAN DARAH SISTOLIK DENGAN OUTCOME STROKE PADA PASIEN DENGAN DAN TANPA INTRACRANIAL LARGE ARTERY STENOSIS - Dedi Sutia; Syarif Indra; Andi Fadilah Yusran Putri; Firstisa Nuzulia K (Jurnal Ilmiah Manuntung, 2020)
Blood pressure in acute onset of ischemic stroke usually increase in patients with intracranial artery stenosis. The aim of increasing blood pressure in this situation is to maintain cerebral autoregulation, meanwhile increased blood pressure in acute onset of ischemic stroke is associated with poor clinical outcomes. This study aims to determine the association between systolic blood pressure and stroke outcomes in patients with and without intracranial large artery stenosis which will help the clinician to determine the prognosis in acute ischemic stroke patients. This study used a cross-sectional design. The population of this study was ischemic stroke patients with or without intracranial arterial stenosis based on the results of transcranial doppler ultrasonography in the neurology department of RSUP Dr. M. Djamil Padang from January 2018 - July 2018. P-value <0.05 was considered statistically significant. In 25 subjects, there were 9 males (36%) and 16 females (64%) based on the gender category.There was a significant difference in systolic blood pressure in both groups (p=0.035). There was no significant difference in MRS values in both groups (p=0.480). There was no significant difference between systolic blood pressure and MRS values in patients with intracranial large artery stenosis (p=0.579) and patients without intracranial large artery stenosis (p=0.481). There was no association between systolic blood pressure and stroke outcome in patients with and without intracranial large artery stenosis.